17. Find the roots of equation x2-5x-6=0.
Answers
Answered by
0
Answer:
Done below
Step-by-step explanation:
The roots are x=2 and x=3 .
Answered by
0
Answer:
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b and c from the original equation and plug them into the quadratic formula.
2
−
5
−
6
=
0
x^{2}-5x-6=0
x2−5x−6=0
=
1
a={\color{#c92786}{1}}
a=1
=
−
5
b={\color{#e8710a}{-5}}
b=−5
=
−
6
c={\color{#129eaf}{-6}}
c=−6
=
−
(
−
5
)
±
(
−
5
)
2
−
4
⋅
1
(
−
6
)
√
Similar questions
Social Sciences,
1 month ago
Biology,
1 month ago
Math,
3 months ago
Environmental Sciences,
11 months ago
Chemistry,
11 months ago
Math,
11 months ago